(The production of Chitosan (Natural Polymer) from Shrim Shells for Additives Uses) - Alamsyah, Rizal; Djubaedah, Endah; Hawani Lubis, enie; Nurdin NK, Mochamad (Warta Industri Hasil Pertanian, 2001)
The study of the productions of chitosan from shrimp and prawn shells using chemical method was conducted to obtain chitosan in relation to food and pharmacy product used. he process of chitosan production consist of demineralization using. HCI, deproteinization and deproteinization have been fullfilled especially for food grade chitosan requirements .the rendemen of chitosan from eaw materials was 14,1% while the viscosity was 23.0 m pas, and the degree of deacetylatuion was 80,23% the disintegration time of sugar coated table was 31 minutes and its weight variation was o,48% meanwhile the moisture content of sugar coated table was 2.4% wet basic .Â Â